Epigenetics as the mediator of fetal programming of adult onset disease: what is the evidence?. (18th June 2014) - Saffery, Richard; Novakovic, Boris
Abstract The Developmental Origins of Health and Disease hypothesis describes how early life environmental factors influence development in a way that impacts later health and disease risk. The hypothesis is supported by a large number of animal studies and a smaller number of observational studies in humans. Epigenetic variation induced in early life has emerged as a prime candidate to be the mediator of such effects, but little direct evidence of this relation exists in humans, primarily due to the inherent problems associated with unraveling the relative contributions of genetic and environmental variables to phenotypic diversity. There are several prerequisites for establishing a causal link that include demonstrating interindividual epigenetic variability in early life in response to specific environmental exposures. Further, compelling evidence linking epigenetic change to disease, prior to onset is required. Finally, the functional relevance of specific epigenetic change must be demonstrated. Evidence is emerging in all of these areas but, ultimately, only large longitudinal life‐course studies, commencing prior to birth, can provide direct evidence in support of a role of epigenetic processes as a driver of Developmental Origins of Health and Disease in humans.